Design and implementation of an open source android mobile barcode inventory software for the University of the Philippines Diliman School of Economics Library - Miclat, John Ezekiel D.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This thesis aimed to augment the prevailing inventory procedures of the University of the Philippines - School of Economics Library by producing an Android mobile inventory software which makes of barcodes affixed on the materials as unique identifiers. It was necessary to produce and implement the software due to the shortage of staff and the massive collection of the library.
The software was designed in accordance with the User Centered Systems Design (UCSD) framework conceptualized by Gulliksen et al. (2003). The software was developed using PHP and MySQL as the backend while HTML and JavaScript were used for the frontend. The Rapid Application Development (RAD) approach as discussed by Kendall and Kendall (2011) was utilized as the development of the researcher. The software was intended to be used with the ZXing Barcode Scanner mobile app for Android due to its open-source nature and its capability to be launched from the web browser.
A comparison between the current manual inventory procedure and the proposed automated inventory procedure was conducted using Time and Motion Study as discussed by Freivalds and Niebel in Niebel's methods, standards, and work design 12th edition. A 54.1% increase in productivity was p by the automated inventory system over the current manual inventory procedure.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Philippines -- Quezon City -- Inventories; Open source software -- Library applications -- Philippines -- Quezon City